“His Soul Is Weeping inside That He Cannot Bury the Dead as before.” Plague and Rebellion in Debrecen (Hungary), 1739–1742 - Ildikó Sz. Kristóf (Religions, 2020)
This is a historical anthropological study of a period of social and religious tensions in a Calvinist city in the Kingdom of Hungary in the first half of the 18th century. The last and greatest plague epidemic to devastate Hungary and Transylvania between cca. 1738 and 1743 led to a clash of different opinions and beliefs on the origin of the plague and ways of fighting it. Situated on the Great Hungarian Plain, the city of Debrecen saw not only frequent violations of the imposed lockdown measures among its inhabitants but also a major uprising in 1739. The author examines the historical sources (handwritten city records, written and printed regulations, criminal proceedings, and other documents) to be found in the Debrecen city archives, as well as the writings of the local Calvinist pastors published in the same town. The purpose of the study is to outline the main directions of interpretation concerning the plague and manifest in the urban uprising. According to the findings of the author, there was a stricter and chronologically earlier direction, more in keeping with local Puritanism in the second half of the 17th century, and there was also a more moderate and later one, more in line with the assumptions and expectations of late 18th-century medical science. While the former set of interpretations seems to have been founded especially on a so-called “internal” cure (i.e., religious piety and repentance), the latter proposed mostly “external” means (i.e., quarantine measures and herbal medicine) to avoid the plague and be rid of it. There seems to have existed, however, a third set of interpretations: that of folk beliefs and practices, i.e., sorcery and magic. According to the files, a number of so-called “wise women” also attempted to cure the plague-stricken by magical means. The third set of interpretations and their implied practices were not tolerated by either of the other two. The author provides a detailed micro-historical analysis of local events and the social and religious discourses into which they were embedded.